FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN KEKURANGAN ENERGI KRONIS (KEK) PADA IBU HAMIL: LITERATUR REVIEW: Factors Influencing the Incident of Chronic Energy Deficiency (CED) to Pregnant Women: Literature Review - Wiqodatul Ummah; Woro Tri Utami (Forind Press, 2024)
Pregnancy is an important period for the formation of the quality of future human resources because growth and development are determined when the fetus is in the womb. The aim of the research is to find and create a clear framework for thinking from what has been formulated in the literature review problem. Secondary data sources obtained in the form of articles or journals that are relevant to the topic are carried out using databases via Google Scholar, PubMed and Research Gate. A literature search was carried out using the keywords